Polémicas y conflictos en torno a la Guerra del Paraguay: los discursos de la prensa en Tucumán, Argentina (1864-1869) - María José Navajas (Centre de Recherches sur les Mondes Américains, 2009)
The press was a key actor of the political life in the nineteenth century. Newspapers and other periodicals exerted an important function inside the political stage, configuring the debates, the disputes, and defining the contenders. This work studies through the press the controversies and conflicts concerning the war against the Paraguay. Our hypothesis is that whereas the war and its phases were not questioned, it did become an important element in the articulation of debates and political disputes. There are two main reasons that sustain this argument: First, the province of Tucumán was not particularly affected during the war; second, the newspapers published during the period of the war, maintained a pro-government orientation. This latter aspect represented a restriction for the message that the provincial press intended to spread along the war.